A study of [Au(ethylenediamine)Cl2]Cl interaction with L-methionine and DL-seleno-methionine by 1H and 13C NMR spectroscopy. Issue 5 (2010) - Al-Maythalony, Bassem A.; Wazeer, Mohamed I. M.; Isab, Anvarhusein A.; Ahmad, Saeed
Abstract : The interaction of [Au( en )Cl2 ]Cl with L-methionine (Met) and DL-seleno-methionine (Se-Met) was carried out in D2 O solution at ∼pH 3.8. 13 C NMR spectra were interpreted by comparison with the spectra recorded after the reaction of Met or Se-Met with HAuCl4 and also after oxidation by H2 O2 . Reactions of [Au( en )Cl2 ]Cl with Met and Se-Met were found to proceed through the exchange of chloride ligands from complex with Met or Se-Met. Gold(III) reduction takes place during the reaction and en ligand was released from [Au( en )Cl2 ]Cl complex.